Hypertension among Diabetes Population in Malaysia and its Associated Risk Factors; Findings from National Health and Morbidity Survey 2015 - Ismail, Hasimah; Saminathan, Thamil Arasu; Omar, Mohd Azahadi; Mat Rifin, Halizah; Robert Lourdes, Tania Gayle; Rodzlan Hasani, Wan Shakira; Jane Ling Miaw Yn,; Ab Majid, Nur Liana; Ahzairin Ahmad,; Mohd Yusoff, Muhammad Fadhli (IIUM Medical Journal Malaysia, 2022)
The prevalence of hypertension and diabetes continue to rise globally. This study aims to examine the national prevalence of hypertension among diabetes population in Malaysia and its associated risk factors. A sub-analysis of data from National Health Morbidity Survey (NHMS) 2015 was conducted among 4229 respondents with diabetes. This data was obtained from respondents aged 18 years and above. Diabetes was defined as those who self-reported to have diabetes or who had fasting capillary blood glucose of ≥6.1 mmol/L or non-fasting blood glucose of >11.1 mmol/L. Hypertension was defined as one who has systolic and diastolic blood pressure of ≥140 and ≥ 90, respectively. The prevalence of hypertension among respondents with diabetes was 57.9% (95%CI: 55.8,60.0). The prevalence of hypertension among diabetes was higher among females (58.7%), ≥60 years old (80.1 %), Chinese (61.1%), those with primary education (69.6%), widow/widower/divorce (75.4%), not working (67.7%), rural residents (60.6%), non-smokers (60.1%), non-drinkers (58.1%), those who were obese (66.0%) and with abnormal cholesterol level (63.5%). Multiple logistic regression analyses revealed that age group, working status, obesity and cholesterol were associated with hypertension among respondents with diabetes. Early detection of hypertension should be an integral part of diabetes management.